Analysis of the exceptional measure of preventive intermission and the right to procedural guarantees of the adolescent in conflict with the criminal law on the reason of the sanitary emergency - Saravia Quispe, José Yván (2020)
In this academic work we will analyze the procedural legal figure of preventive confinement, in order to determine if said measure is being applied within the framework and limits of the procedural guarantees established by the Convention on the Rights of the Child, the Constitution and laws of the specialty. We will reflect on the procedural guarantees that the Judiciary must take into account when deciding on a request for preventive admission. Similarly, we will examine the rights of adolescents deprived of their liberty and which must be guaranteed by the state while they are in their preventive custody, such as the right to health and physical and psychological integrity. Maxima if we are in a situation of health emergency and global pandemic.